Rekonstruksi tujuan pendidikan Islam dalam perspektif Fazlur Rahman - Sehat Sultoni Dalimunthe; Ali Mudin Siregar; Siti Anum; Taupik Juanda Daulay (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This research examines Fazlur Rahman’s perspective on Islamic educational philosophy. Educational philosophy itself is a comprehensive and organized reflection on issues related to learning, such as curriculum, teachers, and students. Although it shares similarities with general educational philosophy, the Islamic version is grounded in teachings derived from the Qur’an and the Sunnah. According to Fazlur Rahman, the core purpose of Islamic education is to worship God by nurturing human potential in harmony with divine guidance and personal responsibility. The study uses literature review methods and textual analysis of books, journals, theses, and other documents connected to Rahman’s ideas. Findings indicate that Rahman views education as the primary means for serving God, which includes developing one's abilities according to divine commands and using nature responsibly. For him, the ultimate aim of education is the integral growth of human potential intellectually, morally, and spiritually so that individuals not only excel academically but also possess strong ethical and social awareness. Islamic education, therefore, is understood as a continuous effort to form a complete human being committed to the progress of civilization.